Implantes transmaxilares longos melhoram a qualidade de vida em pacientes com maxilas atróficas - Kopp, Gino (2020)
The advancement of contemporary dentistry is related to the improvement of existing techniques, materials, and technology, always in the sense of improving people's oral health, which can ultimately reflect to a better quality of life. The aim of this study was to evaluate the quality of life (QoL) of patients with atrophic jaws, submitted to insertion of long transmaxillary implants and posterior prosthetic rehabilitation. Twelve patients (n = 12), of both sexes, with a mean age of 55.83 ± 2.78 years old, that were unable to receive conventional implants immediately, due to lack of bone, received two long transmaxillary implants in a horizontal position, anteroposteriorly, one on each side, from the canine pillar to the maxillary tuberosity. After six months, the conventional clinical sequence for making a fixed prosthesis type protocol or removable prosthesis type overdenture (MK1® system) was performed. The Oral Health Impact Profile questionnaire (OHIP-14) was applied preoperatively, and six months after the installation of the rehabilitation with dental prosthesis on the implants. The results were submitted to statistical analysis with a significance level of 0.05. It was possible to observe an improvement in the perception of QOL between the pre and postoperative periods in the OHIP-14 total score and in the domains related to functional limitation (D1), physical pain (D2), psychological discomfort (D3), physical disability (D4), psychological disability (D5), social disability (D6) and handicap (D7) (p < 0.05). It is possible to conclude that long transmaxillary implants rehabilitation improves quality of life in patients with atrophic maxilla.